Make the farm attractive - Jones Jr., Isaac (My University, 1894)
Introduction: In reviewing the progress of our country for the past century we are struck by the wonderful changes that have taken place along all lives. We see steam taking the place of horse hooves to be in turn replaced by electricity: We see small one story buildings replaced by magnificent structures towering to the skies; We see immense bridges suspended in midair and on every hand we see the wonderful transformation due to the inventor and the mechanic. As we note the difference in our country as she is today and the United States of one hundred years ago our growth seems truly marvelous; and it seems almost impossible to make a comparison between the struggling states that then bordered the Atlantic and the glorious nation that in the language of another “sweeps so grandly from ocean to ocean across a continent.” These changes have developed characteristics in the population of our country that were unknown one hundred years ago.
Citation: Jones Jr., Isaac. Make the farm attractive. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Farm; Agriculture; Industrial; Machinery; Theses; Manuscripts (documents)